Instructional design models for online instruction: from the perspective of Iranian higher education - Khodabandelou, Rouhollah; Abu Samah, Siti Akmar (Elsevier, 2012)
Today, online instruction is a new approach among many higher education institutions and is also becoming more prevalent in higher education. In terms of importance and effectiveness of online instruction in academic achievements, motivation and attitudes of students, this study investigates current uses of instructional design (ID) models in designing and developing online instruction for higher education. The purpose of this study is to understand how ID models are being used in the design and development of online instruction. It is also to identify which elements of an ID model are necessary in developing online instruction. In order to address the research objectives, a Delphi research methodology was employed. The population of this study consists of academicians who are actively involved in the instructional design activities of online instruction with particular focus on the Iranian higher education. The instrument to gather the data for this descriptive research was a survey questionnaire. A survey questionnaire was designed and executed to collect the necessary data which will then be coded and analyzed using SPSS.